Desarrollo de productos para el fomento del turismo rural en el destino Puerto López - Cedeño Salvatierra, Byron Javier (2019)
The objective of this research was to develop products for the promotion of rural tourism in the destination of Puerto López, generating a dynamisation of the local economy. They type of research adopted was mixed with a descriptive approach in which three phases were proposed, beginning with the comprehensive tourism diagnosis that, through several instruments, allowed to determine, that despite the limitation of alternative tourism products, Puerto López meets the necessary conditions and basic references to the elements of the tourist system with certain deficiencies where the problems lie in the incipient planning and decision-making process, 12 natural and 8 cultural attractions within its rural environment were also identified. The second phase corresponds to the design of tourism products based on the study of supply and demand in addition to the analysis of tourism potential. The Machalilla National Park and Los Frailes Beach stand out as the greatest potential, and the San Sebastian Cloudy Forest and Puerto López Beach are the emerging potential. Based on the study of the canton, the proposal La Bahía del Encanto and Tour Puerto López Rural were carried out, in which adventure activities are displayed as enjoying the beach, the mountains and the typical gastronomy of the area. The plaza focuses on strategic points in Manabí. Phase three corresponds to the action plan, which establishes a series of activities that allow the implementation of tourism products which represents a total cost of $ 64,100.00.